A nation of immigrants the Chinese-American experience - McGlincy, Felice; Agency for Instructional Technology; Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 2003)
Discusses immigration to the United States during the 19th and 20th centuries, with particular emphasis on movement to the western region by immigrants from China.
Closed-captioned.
DVD.
Host: Ellen Gilberti.
Originally released in 1991.
Keywords: Chinese Americans; United States -- Emigration and immigration -- Social aspects; West (U.S.) -- Emigration and immigration -- Social aspects; Films for hard of hearing people